SPINAL CORD INFARCTION DUE TO NEUROFIBROMATOSIS TYPE 1 ASSOCIATED VASCULOPATHY. Issue 12 (15th November 2016) - Lavin, Tim; Murphy, Christopher; Ealing, John; Herwadkar, Amit
Abstract : We report a 28 yr old woman presented with acute onset lower limb weakness, urinary retention and back pain. She has a history of neurofibromatosis type 1, epilepsy, Henoch Schonlein purpura, IgA nephropathy and hypertension. Examination revealed lower limb paraplegia, lower limb areflexia, patchy loss of pain and temperature to knees and preserved proprioception. MR imaging confirmed a T10 spinal cord infarction. CT angiography confirmed stenotic and aneurysmal changes affecting aorta, renal and infrarenal vessels. Similar changes were seen on CT angiography in 2010, when she was investigated for IgA Nephropathy. The changes are consistent with the changes seen in vascular dysplasia associated with NF1. Cerebrovascular dysplasia is reported in NF1. Incidence is between 2–5%.1 Dysplastic vascular abnormalities affecting other vessels, including aorta, renal, infrarenal and mesenteric is recognised.2 Most are asymptomatic, and more common in the paediatric population. To our knowledge spinal cord infarction due to NF1 vascular dysplasia has not been reported.